2020
DOI: 10.1002/jclp.23019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of scrupulosity: Associated symptoms and comorbidity

Abstract: Objective: Scrupulosity is a manifestation of obsessivecompulsive disorder (OCD) characterized by religious or moral core fears. Clinicians often struggle to treat scrupulosity, which may be associated with several features known to predict poor treatment outcome. The purpose of this study was to examine these features in participants with scrupulous OCD, contamination OCD, and healthy controls. Method: A total of 68 participants (57.4% women, age mean = 34.01) completed diagnostic interviews, and measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Contrary to expectations, religiosity did not correlate with scrupulosity (see Abramowitz and Buchholtz 2020). Although a number of studies demonstrated positive associations between religiosity and religious scruples (Siev et al 2021), some previous studies did not show significant associations between these variables (Nelson et al 2006). The associations between religiosity and scrupulosity, therefore, seem to be complex and could depend on the particular cultural context (Abramowitz and Jcoby 2014).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Contrary to expectations, religiosity did not correlate with scrupulosity (see Abramowitz and Buchholtz 2020). Although a number of studies demonstrated positive associations between religiosity and religious scruples (Siev et al 2021), some previous studies did not show significant associations between these variables (Nelson et al 2006). The associations between religiosity and scrupulosity, therefore, seem to be complex and could depend on the particular cultural context (Abramowitz and Jcoby 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Mental health professionals, and also patients, have problems with differentiating between the normative religious struggle and pathological symptoms of scrupulosity. Religious doubts and rituals may appear to be similar to compulsive rituals and obsessions present in a mental disorder (e.g., OCD; Siev et al 2021). The question of how religious individuals become scrupulous is similarly under-studied (Siev et al 2017b).…”
Section: A Network Analysis Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Scrupulosity is a sub-type of obsessive-compulsive disorder (OCD) that involves moral and religious anxieties and rigidity. Characteristics associated with scrupulosity include perfectionism, self-doubts, discomfort with uncertainty, persistent and tormenting thoughts interpreted as “immoral” or sacrilegious, poor insight, and depression (Besharat & Kamali, 2016; Siev et al, 2021). For example, a scrupulous person likely will feel anxiety about not having enough faith or not being saved, or not being pure or pious enough.…”
mentioning
confidence: 99%